Maize Seed Germination Under Low-Temperature Stress Impacts Seedling Growth Under Normal Temperature by Modulating Photosynthesis and Antioxidant Metabolism - Meng, Aiju; Wen, Daxing; Zhang, Chunqing (Frontiers in Plant Science, 2022)
Spring maize is usually subjected to low-temperature stress during seed germination, which retards seedling growth later even under a suitable temperature. However, the mechanism underlying maize seed germination under low-temperature stress impacting seedling growth is still ambiguous. In this study, we used one low-temperature sensitive maize (SM) and one low-temperature resistance maize (RM) to investigate the mechanism. The results showed that the SM line had higher malondialdehyde content and lower total antioxidant capacity (TAC) and germination percentage than the RM line under low-temperature stress, indicating the vulnerability of SM line to low-temperature stress. Further transcriptome analysis revealed that seed germination under low-temperature stress caused the down-regulation of photosynthesis-related gene ontology terms in two lines. Moreover, the SM line displayed down-regulation of ribosome and superoxide dismutase (SOD) related genes, whereas genes involved in SOD and vitamin B6 were up-regulated in the RM line. Kyoto Encyclopedia of Genes and Genomes enrichment analysis revealed that photosynthesis and antioxidant metabolism-related pathways played essential roles in response to low-temperature stress during seed germination. The photosynthetic system displayed a higher degree of damage in the SM line. Both qRT-PCR and physiological characteristics experiments showed similar results with transcriptome data. Taken together, we propose a model for maize seed germination in response to low-temperature stress.